Effect of White Kidney Bean Powder on Quality Characteristics of Dough and Biscuits - Ruxiao SHEN; Haoguo TANG; Tongxiang YANG; Qihe SI; Jiakang WANG; Kaili LI; Chenhuan WANG (Shipin gongye ke-ji, 2025)
To investigate the effects of white kidney bean flour on the quality characteristics of dough and biscuits, white kidney bean flour (0~50%) was added to low-gluten flour, and the physicochemical properties, gelatinizing properties, rheological properties of dough, as well as the texture characteristics, moisture distribution, secondary structure of protein, disulfide bond content, and quality characteristics of biscuits of the composite flours at different ratios were examined. The results showed that with the increase in addition of white kidney bean flour, the water-holding capacity of the composite flour significantly improved (P<0.05), while the oil-holding capacity decreased. The retrogradation value decreased from 1585 cP to 1084 cP, effectively inhibiting starch retrogradation. Additionally, the addition of white kidney bean flour increased the storage modulus (G') and loss modulus (G") of the dough and reduced the content of free water in the biscuits. When the addition of white kidney bean flour was 30%, the hardness and chewiness of the biscuits were 3311.17 g and 94.54 g, respectively, which were higher than those of the control group (0%). At this addition level, the α-helix content of the biscuits increased to 28.04%, and the micromechanism was similar to that of the control group. At this addition level, biscuits were characterized by uniform color, high acceptability, and prominent bean flavor, achieving the highest sensory score. In summary, the quality of biscuits was optimal when the addition of white kidney bean flour was 30%. This study provides a basis for further development and utilization of white kidney bean flour in the field of baked products.